Innovation of a 3D pop-up book and culturally-based animated film as positive stimulation for children with attention deficit hyperactivity disorder (ADHD) - Listiana, Ida; Kasumawati, Frida; Hadi, Talitha El Zhafira; Indah, Fenita Purnama Sari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Attention Deficit Hyperactivity Disorder (ADHD) is a common problem in the medical, psychological, and even educational fields. ADHD is the third most common mental illness after depression and anxiety disorders. Indonesia has a population of 82 million children, with one in five children and adolescents under 18 experiencing mental health problems, including ADHD. Therefore, it is important to develop positive stimulation media for children with ADHD. Purpose: To develop and test the effectiveness of positive stimulation media that is easy to use while introducing Indonesian culture to attract the interest of children with Attention Deficit Hyperactivity Disorder (ADHD). Method: This research uses a mixed method exploratory research that combines quantitative and qualitative research approaches. 3D Pop Up Book media and culturally based educational animated films are packaged according to the child's age category with attractive colors and storylines with typical Indonesian characters complete with accents and batik. So that children will be able to focus more and stimulate their brain function. Results: This research has successfully developed 3D Pop Up Book media and culturally based educational animated films designed to support positive stimulation for children with ADHD. The development process began with a Focus Group Discussion (FGD) with psychologists, pediatricians, health promotion experts, animators, teachers, and parents of children with ADHD, which generated input regarding media needs, visual design, and appropriate cultural content. The FGD results emphasized the importance of media that is engaging, easy to understand, and able to channel children's energy through visual and motor activities. Testing on children with ADHD showed significant changes in distractible behavior. In the pretest, 33.3% of children were in the low category, 40% in the medium category, and 26.7% in the high category. After the intervention, the proportion increased in the low category (53.3%) and decreased in the high category (16.7%). Analysis using the Wilcoxon Signed Rank Test showed a p-value of 0.049, indicating a significant difference before and after the intervention. Conclusion: These findings indicate that this culture-based media is not only innovative but also effective in reducing distractible behavior in children with ADHD.